Experiences of pain among Palestinian advanced cancer patients: a socio-cultural reading of reports from the Israeli occupied West Bank - Giacaman, Rita; Hammoudeh, Weeam; Mitwalli, Suzan; Husseini, Abdullatif; Harding, Richard (Frontiers in Psychiatry, 2025)
IntroductionThis paper explores how pain is conceptualized, defined, expressed and managed among Palestinians with advanced cancer living in the Israeli occupied West Bank of the river Jordan.MethodsUtilizing qualitative methodology, the study was conducted in three Palestinian governmental hospitals located in the north, center and south of the West Bank. We used a socio-cultural lens which frees our writing from subjugation, and exposes further the need to continue decolonizing knowledge production. Verbatim colloquial Palestinian Arabic quotes obtained from research participants were extracted and translated to English with a focus on meaning rather than semantics, as meaning is deeply embedded in culture. These quotes were then integrated into the text to illustrate the identified themes and subthemes accompanied by selected information about the participant including age, gender, residence, and cancer diagnosis to provide context. We have included in the text the Arabic colloquial terms written in both Arabic and English.ResultsTwo dimensions of pain were reported: physical pain due to the effects of the cancer and its treatment, and existential pain, which we defined as the sum total of the human experience of having and dealing with cancer physically, psychologically, socially, economically and spiritually. In addition to treatment with cancer medications, participants emphasized that social support and solidarity from families, friends, neighbors and their community play an important role in helping them come to terms with their illness and pain, and standing by them during difficult times.DiscussionThis social support/social solidarity, is generally regarded as a wajib (واجب), or obligation and duty people must fulfill and cannot be neglected. Dependence on God (Allah) and Tawwakul, that is, the reliance on Allah, which they drew upon for support and endurance, was also emphasized. The notion of Tawwakul and reliance on Allah is of particular importance in assisting patients and their families in coming to terms with their sickness and pain, and in confronting death, as revealed by our participants. However, the incorrect interpretation of Tawwakul as fatalism is rooted in colonial and racial perspectives, and needs to be addressed and undone in the process of decolonizing knowledge production.